2014
DOI: 10.7554/elife.04066
|View full text |Cite
|
Sign up to set email alerts
|

Broad and direct interaction between TLR and Siglec families of pattern recognition receptors and its regulation by Neu1

Abstract: Both pathogen- and tissue damage-associated molecular patterns induce inflammation through toll-like receptors (TLRs), while sialic acid-binding immunoglobulin superfamily lectin receptors (Siglecs) provide negative regulation. Here we report extensive and direct interactions between these pattern recognition receptors. The promiscuous TLR binders were human SIGLEC-5/9 and mouse Siglec-3/E/F. Mouse Siglec-G did not show appreciable binding to any TLRs tested. Correspondingly, Siglece deletion enhanced dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
138
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(146 citation statements)
references
References 52 publications
3
138
1
1
Order By: Relevance
“…In a recent study, it was shown that many Siglecs (including Siglec-E) can bind to sialic acids on Toll-like receptors and could potentially act as a brake to slow down or resolve inflammation (13). Removal of sialic acids with sialidase Neu1 can disrupt this interaction, resulting in activation of inflammatory processes.…”
Section: Cd33-related Siglecs Are a Family Of Proteins Widely Expressmentioning
confidence: 99%
“…In a recent study, it was shown that many Siglecs (including Siglec-E) can bind to sialic acids on Toll-like receptors and could potentially act as a brake to slow down or resolve inflammation (13). Removal of sialic acids with sialidase Neu1 can disrupt this interaction, resulting in activation of inflammatory processes.…”
Section: Cd33-related Siglecs Are a Family Of Proteins Widely Expressmentioning
confidence: 99%
“…Therefore, here the levels of TNF-␣ protein are used as readout of endotoxin tolerance. TNF-␣ in the culture supernatants was measure using the CBA Beads kit as previously described (23)(24)(25). As shown in Fig.…”
Section: Sialylation Of Cell Surface Was Significantly Increased On Lmentioning
confidence: 99%
“…Previously, we found that Siglec G/10-CD24 interaction selectively represses the NF-B-driven inflammatory response to danger-associated molecular patterns (DAMPs), 2 but not pathogen-associated molecular patterns (PAMPs) (23,24). Recently, we reported extensive and direct interactions between Siglecs and Toll-like receptors (TLRs) and dendritic cells from Siglece-deficient mice demonstrated increased responses to all TLR ligands tested (25). However, whether Siglecs contribute to the development of endotoxin tolerance is still unknown, and further experimental investigation is needed to delineate this and identify effective targets for sepsis therapy.…”
mentioning
confidence: 99%
“…Of these, Neu3 is predomi nantly localized in the plasma membrane, and both Neu1 and Neu4 have been found to translocate to the cell surface under certain conditions, while Neu2 is a cytosolic enzyme [104]. Neu5Ac2en 14, and its C5 glycolamido analog, have been shown to disrupt that activity of Neu1 at the cell surface [123]. Studies using recombinant human sialidases, showed that 4-deoxy-4-guanidino-Neu5A c2en 5 produces only weak inhibition of Neu1 (IC 50 2.7 mM) and Neu4 (IC 50 0.5 mM), but a micromolar level of inhibition against Neu2 (IC 50 16 μM) and Neu3 (IC 50 6.8 μM) [124].…”
Section: Selectivity For Influenza Virus Sialidase Over Human Sialidasesmentioning
confidence: 99%